5G Independent Smart Pole - Heba Y. M. Soliman (International Telecommunications Society (ITS), 2019)
This paper presents a model of an energy independent smart pole operating under the 5G technological umbrella. Types of sensors necessary for the smart cities operation are described. Suitable Sustainable energy sources for the pole operation are presented.
Keywords: 330; sustainable smart city; independent smart pole